2019
DOI: 10.1088/1757-899x/558/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Combined equipment for synthesis of ultrafine metals and metal compounds powders via Flow-Levitation and crucible methods.

Abstract: Laboratory automated equipment for synthesis of ultrafine particles of metals, alloys and metal compounds via evaporation-condensation Flow-Levitation Guen-Miller method combined with crucible method using high-frequency (440 kHz) electromagnetic field for heating is described. The equipment synthesizes the said particles and multilayer core-shell structures with mean size ranging from tens to hundreds of nanometers with output from grams to tens of grams per hour. Synthesized particles may be collected into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Smooth spherical nickel nanoparticles were prepared by the flow-levitation method. 31 The micrograph of the grains is shown in Fig. 1.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…Smooth spherical nickel nanoparticles were prepared by the flow-levitation method. 31 The micrograph of the grains is shown in Fig. 1.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…The material studied has been thoroughly described in our previous work [ 10 ]. Briefly, nanosized nickel particles (nNi) were synthesized using the flow-levitation method [ 18 ]. X-ray diffraction analysis demonstrated that the particles consisted primarily of metallic nickel with a small NiO x oxide content of less than 0.3% weight.…”
Section: Materials Properties and Samplesmentioning
confidence: 99%
“…Therefore, in this work, we consider a new method of induction flow levitation for obtaining high-purity nickel nanoparticles. This method makes it possible to obtain nanosized particles with a narrow size distribution directly from bulk metal samples without the use of auxiliary reagents, which distinguishes it favorably from other methods for the synthesis of nanoparticles [19][20][21]. The resulting nanoparticles were characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (SEM-EDS), Xray phase analysis (XRD), transmission electron microscopy (TEM), and porosimetry.…”
Section: Introductionmentioning
confidence: 99%